A comprehensive review of the soil health status for enhancing agricultural sustainability - Timilsina, Raja Rajendra; Khosla, Sunil; Rahut, Dil B.; Jena, Pradyot Ranjan; Sonobe, Tetsushi (Frontiers in Environmental Science, 2025)
Sustainable agricultural practices have become more crucial than ever as the world grapples with food insecurity and environmental degradation. Soil health, a fundamental attribute of agricultural productivity and ecosystem stability, plays a pivotal role in achieving global sustainability targets. Despite its importance, comprehensive analyses of soil health initiatives remain limited. This systematic review addresses this gap through a dual objective: first, to contextualize the critical role of soil health in advancing the Sustainable Development Goals (SDGs); and second, to critically evaluate the implementation, impact, and policy relevance of India’s Soil Health Card (SHC) scheme launched in 2015 to enhance soil fertility through site-specific assessments and tailored fertilizer recommendations. Global research highlights the crucial role of soil health in promoting sustainable agriculture, and the SHC scheme has yielded notable results, including a 5%–6% increase in crop yields and an 8%–10% decrease in chemical fertilizer usage. Grounded in the framework of the SDGs, this paper highlights the SHC scheme’s contributions to enhancing farm productivity, lowering input costs, and advancing environmental objectives. It further explores the policy landscape, identifies institutional gaps, and examines the potential for scaling and adapting these practices in other regions. This review offers evidence-based insights into the interplay between soil health, agricultural sustainability, and policy innovation, aiming to inform future interventions and promote international collaborations in sustainable land management.